2003
DOI: 10.1021/ja021327y
|View full text |Cite
|
Sign up to set email alerts
|

Sanglifehrin−Cyclophilin Interaction:  Degradation Work, Synthetic Macrocyclic Analogues, X-ray Crystal Structure, and Binding Data

Abstract: Sanglifehrin A (SFA) is a novel immunosuppressive natural product isolated from Streptomyces sp. A92-308110. SFA has a very strong affinity for cyclophilin A (IC(50) = 6.9 +/- 0.9 nM) but is structurally different from cyclosporin A (CsA) and exerts its immunosuppressive activity via a novel mechanism. SFA has a complex molecular structure consisting of a 22-membered macrocycle, bearing in position 23 a nine-carbon tether terminated by a highly substituted spirobicyclic moiety. Selective oxidative cleavage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 37 publications
0
91
0
1
Order By: Relevance
“…Protein Data Bank revealed that the overall fold is most closely related to the human (1NMK) and the Plasmodium (1QNH) Cyp structures (47)(48)(49). The biggest difference from the human structure is the presence of additional residues that are found in the plant and parasite species after the first ␣-helix (Fig.…”
Section: Identification and Cdna Cloning Of The 18-kda Allergen;mentioning
confidence: 97%
“…Protein Data Bank revealed that the overall fold is most closely related to the human (1NMK) and the Plasmodium (1QNH) Cyp structures (47)(48)(49). The biggest difference from the human structure is the presence of additional residues that are found in the plant and parasite species after the first ␣-helix (Fig.…”
Section: Identification and Cdna Cloning Of The 18-kda Allergen;mentioning
confidence: 97%
“…The crystal structures of SfA and a semisynthetic derivative bound to CypA have been published (26) and reveal that they both bind to the same active site as CsA. SfA analogues devoid of immunosuppressive properties have been synthesized (44), indicating an opportunity for the design of nonimmunosuppressive Cyp inhibitors for potential use in HCV therapy.…”
mentioning
confidence: 99%
“…Except for the functions mentioned above, CypA also plays a critical part in the replication of various kinds of viruses, such as human immunodeficiency virus type 1 (HIV-1), influenza virus, HCV, vesicular stomatitis virus (VSV), vaccinia virus and human papilloma virus (HPV) [10,11]. On account of the importance of CypA in the regulation of numerous biological processes, significant efforts have been made in the discovery of CypA inhibitors in the past decade [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%